2013
DOI: 10.5539/ass.v9n13p137
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Parent and Peer Influences on Hedonistic Behavior among Undergraduate Students in Malaysia

Abstract: This study assesses the moderating influence of parental and peer attachment on hedonistic behavior among a sample of youth in Malaysia. Using Bronfenbrenner’s theory of human ecology and Armsden and Greenberg’s attachment model, this study examines the direct and indirect influence of religiosity and worldview on the development of hedonistic behavior as moderated through parental and peer attachment. Drawing on a quantitative survey of 408 Malaysian university students (M age = 21.0, SD = .40), structural eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…Religious concepts from Islamic perspective have been described through the model of Muslim Religiosity developed by Azimi Hamzah et al (2007), which consists of two elements, namely the Islamic worldview and Muslim personality. Azimi et al (2007) develop the concept of Muslim religiosity through three basic dimensions: Islam, iman (faith) and ihsan (courtesy).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Religious concepts from Islamic perspective have been described through the model of Muslim Religiosity developed by Azimi Hamzah et al (2007), which consists of two elements, namely the Islamic worldview and Muslim personality. Azimi et al (2007) develop the concept of Muslim religiosity through three basic dimensions: Islam, iman (faith) and ihsan (courtesy).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Religious concepts from Islamic perspective have been described through the model of Muslim Religiosity developed by Azimi Hamzah et al (2007), which consists of two elements, namely the Islamic worldview and Muslim personality. Azimi et al (2007) develop the concept of Muslim religiosity through three basic dimensions: Islam, iman (faith) and ihsan (courtesy). A study by Raida Abu Bakar, Fang Lee Cooke and Nuttawuth Muenjohn (2016) found that Islamic religiosity seems to be evident in the moral reasoning and the management of behaviour at the workplace.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kelekatan teman sebaya atau peer attachment merujuk pada suatu kelompok yang menjadi acuan bagi remaja dalam menentukan perilaku atau nilai dalam perkembangan kognisi dan emosi yang belum matang (Sukarno et al, 2018). Teman sebaya ikut berperan dalam pengembangan nilai-nilai yang menghasilkan kebahagiaan dan kepercayaan diri, yang pada gilirannya menghasilkan sikap dan perilaku positif (Hamzah et al, 2013;Jusoh et al, 2015).…”
unclassified